Case report: A novel APTX p.Ser168GlufsTer19 mutation in a Chinese family with ataxia with oculomotor apraxia type 1 - Wu, Xuan; Dong, Nan; Liu, Zhensheng; Tang, Tieyu; Liu, Meirong (Frontiers in Neurology, 2022)
Ataxia with oculomotor apraxia type 1 (AOA1) is a rare genetic disorder and is inherited in an autosomal recessive manner. It is mainly characterized by childhood-onset progressive cerebellar ataxia, with dysarthria and gait disturbance being the two most common and typical manifestations. Axonal sensorimotor peripheral neuropathy, dystonia, chorea, and cognitive impairment are common associated symptoms, as are hypoalbuminemia and hypercholesterolemia. Oculomotor apraxia (OMA) has been reported to be a feature often, although not exclusively, associated with AOA1. The Aprataxin gene, APTX, is ubiquitously expressed, and numerous APTX mutations are associated with different clinical phenotypes have been found. In the present study, we enrolled a 14-year-old boy who developed ataxia with staggering gait from the age of 4 years. Early-onset cerebellar ataxia, peripheral axonal neuropathy,cognitive impairment and hypoalbuminemia, hypercholesterolemia were presented in this patient, except for OMA.We applied ataxia-related genes filtering strategies and whole-exome sequencing (WES) to discover the genetic factors in a Chinese family. Sanger sequencing was used in the cosegregation analysis in the family members. A compound heterozygous mutation in APTX gene (c.739C>T and c.501dupG) was identified. This is the first description of a genetically confirmed patient of AOA1 in a Chinese family in addition to a novel mutation of c.501dupG in APTX.